GOOD TOURISM GOVERNANCE DI POS BLOC MEDAN DALAM MENCIPTAKAN INOVASI DAN PERTUMBUHAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KOTA MEDAN - Tesalonika Gultom; Victor Lumbanraja (CV. Denasya Smart Publisher, 2025)
This study aims to analyze Good Tourism Governance (GTG) at Pos Bloc Medan in creating innovation and the growth of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. Pos Bloc Medan is a creative space developed through the revitalization of a heritage building, playing a strategic role in supporting the creative economy and tourism sectors in Medan City. However, the management of this area still faces several challenges, including limited involvement of local communities in decision-making, unequal access to participation for MSME actors, dominance of larger-scale businesses, weak engagement from the local government, and suboptimal waste management and supporting infrastructure.This research adopts a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Informants include Pos Bloc Medan’s management, MSMEs actors, visitors, and the Medan City Tourism Office. The findings reveal that GTG principles have been implemented, including community participation, stakeholder involvement, local ownership and partnership, sustainable resourse use, accommodation of public aspirations, program monitoring and evaluation, environmental accountability, community training, and promotion of local cultural values, although many of these practices remain informal.The application of GTG has proven to positively contribute to the creation of inclusive spaces that stimulate product innovation, strengthen local branding, and and the growth of local MSMEs. Therefore, it is necessary to reinforce participatory and collaborative principles in the governance of Pos Bloc Medan. The management is expected to expand access and equal opportunities for local MSMEs, while increasing community involvement in planning and implementation. Moreover, local government must play an active role in formulating collaborative and sustainable policies to build a fair, innovative, and has a broad impact on local MSME actors.